2007
DOI: 10.1002/jcla.20139
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphism of thymidylate synthase, but not of the COMT and IL‐1B genes, is associated with breast cancer

Abstract: Polymorphic variations may affect the rate of gene transcription, the stability of the mRNA, or the quantity and activity of the resulting protein. In this study we evaluated the association between the interleukin-1B C-31T, catechol-O-methyltransferase Val158Met, and thymidylate synthase (TS) 1494del6 polymorphisms and breast cancer. Each genetic polymorphism was investigated by polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) analysis. No significant difference in either the geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
2
21
1
Order By: Relevance
“…Nevertheless, we should consider that the findings on cancer risk are controversial, with positive, negative or null results. [25][26][27][28][29][30][31][32] Different hypotheses have been proposed to explain the observed discrepancies. It might reflect differences in the gene-disease association (that is, different types of cancer, different association) or may reflect different intakes of micronutrients, folate and B vitamins in particular, in the different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we should consider that the findings on cancer risk are controversial, with positive, negative or null results. [25][26][27][28][29][30][31][32] Different hypotheses have been proposed to explain the observed discrepancies. It might reflect differences in the gene-disease association (that is, different types of cancer, different association) or may reflect different intakes of micronutrients, folate and B vitamins in particular, in the different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the data reported by Liu et al [1] for the study reported by Akisik et al [3] did not seem to agree with the data from Akisik et al's study [3] in their original publication. The numbers reported by Akisik et al [3] for the TT and CC genotypes were 45 and 18 among the cases and 33 and 21 among the controls, respectively (shown in Table 2 of Akisik et al's original paper). Interestingly, after carefully examining the data reported by Liu et al [1], the numbers for TT and CC were 18 and 45 among the cases and 21 and 33 among the controls, respectively (shown in Table 1 of Liu et al's paper) [1].…”
mentioning
confidence: 77%
“…Interestingly, after carefully examining the data reported by Liu et al [1], the numbers for TT, CT and CC were 185, 313 and 133 among the cases and 88, 175 and 102 among the controls, respectively (shown in Table 1 of Liu et al's paper) [1]. Second, the data reported by Liu et al [1] for the study reported by Akisik et al [3] did not seem to agree with the data from Akisik et al's study [3] in their original publication. The numbers reported by Akisik et al [3] for the TT and CC genotypes were 45 and 18 among the cases and 33 and 21 among the controls, respectively (shown in Table 2 of Akisik et al's original paper).…”
mentioning
confidence: 94%
“…However, in the methods, they stated that ''The following criteria were used to select the eligible studies… (d) a genotype distribution among the control populations consistent with Hardy-Weinberg Equilibrium (HWE).'' Of the ten studies, the genotype distributions among the control populations in two studies were not in agreement with HWE [3,4]. Thus, the two studies did not meet the inclusion criteria and should be excluded.…”
mentioning
confidence: 99%
“…Nevertheless, the meta-analysis showed a modest association in the overall population (All in HWE) when the Caucasian study by Justenhoven et al [2] was included in the analysis (P = 0.03). Furthermore, for the TS3 0 -UTR polymorphism, only two studies were conducted in the Caucasian population under homozygote comparison, and, of the two studies, the genotype distributions of controls in one study were not in agreement with Hardy-Weinberg equilibrium (HWE) [3]. There may be no enough power to detect a significant association of the TS3 0 -UTR polymorphism with BC in the Caucasian population.…”
mentioning
confidence: 99%